Implementasi Pure Data Programming Untuk Generate Real-Time Game Audio Synthesis Pada Platformer Game - Bariq Najmi Rizqullah Kartiko Putro; Eriq Muhammad Adams Jonemaro; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Audio plays a very important role in the game besides the another component of game development. Traditional audio technology has its foundations in recording. By using the recording processs, the result obtained are a series of amplitude waves, which contain sounds from recording. The result of the recording produce a data. The storage space needed to store a sound data is every 1 minute of stereo sound with a 44,1 kHz sample rate requires 10 megabyte of storage space. There is an audio technology that can be used in game development. Pure Data is visual programming language for multimedia purpose. Pure Data can be used to process and generate sound, video, 2D or 3D graphics and MIDI for sound engineering purpose. Furthermore, there is framework called Heavy for easily generating audio plugins, used in implementating Pure data to Unity. Heavy make use of modern software pronciples to generate highly optimized code. In this study discussed the sound effects and background music. Sound assets will be implemented into the game. The result of this study are the comparison of document sizes of the three types of sound, sound eefect, background music, and main menu music. Pure Data generate procedural audio which is a dynamic type of audio. The advantage of dynamic audio is sound effects that contribute to emotional involvement of the player. Heavy framework is used to implement Pure Data to unity. There are two types of testing Pure Data, unit testing and validation.